ANTIMICROBIAL ENHANCEMENT OF GLASS IONOMER CEMENT WITH PHYTOMEDICINE - Mishra, Anwesha; Kumar, Gunjan; Menon, Ipseeta; Singh, Arpita; Dash, Kabir Suman; Swain, Asheerbad (Eastern Ukrainian Medical Journal, 2026)
Background: Glass ionomer cement (GIC) is widely used in restorative dentistry because of its ability to release fluoride, its compatibility with biological tissues, and its chemical bonding with tooth structures. However, its inherently limited antimicrobial properties make restorations susceptible to bacterial growth and the development of secondary cavities. The integration of phytomedicines – bioactive compounds derived from plants – has been identified as a promising approach to boost the antimicrobial capabilities of GIC while maintaining its mechanical integrity. Aim: This review aims to explore and synthesize current evidence on the modification of Glass Ionomer Cement with phytomedicinal agents. Methods: Literature search was conducted using electronic databases including PubMed and Google Scholar, focusing on articles published in the English language between 2014 and 2024. Only in vitro studies evaluating antibacterial activity as a primary outcome were included, while mechanical properties were considered when reported alongside antimicrobial testing. This review collected evidence from in vitro studies evaluating GIC modified with herbal extracts such as Azadirachta indica (neem), Curcuma longa (turmeric), Thymus vulgaris (thyme), Triphala, propolis, Salvadora persica (miswak), and Acacia nilotica (babool). The antibacterial activity against cariogenic microorganisms, primarily Streptococcus mutans and Lactobacillus species, and compressive strength were assessed. Results: Most modified GIC formulations demonstrated enhanced antibacterial activity with surface antimicrobial characteristics compared with conventional GIC. Several studies also reported preserved or improved compressive strength at optimal extract concentrations. Conclusion: Phytomedicine-infused GIC shows promise as a biocompatible and cost-effective restorative material. However, further standardization and in vivo studies are required to validate clinical efficacy and safety.